Mulching Effects on Stress Management of Cotton in Relation to Irrigation and Nitrogen Levels - Joshi, Ritika; Singh, C. B. (International Journal of Bio-resource and Stress Management, 2018)
Severity of increasing temperature worldwide presents an alarming threat to crop production. Wider row-to-row and plant-to-plant spacing and high temperature lead to higher rate of evaporation and stress to cotton production. Effect of mulching on stress (water, nutrient and heat) and their associated effects on leaf water potential, canopy temperature, NDVI and SPAD value were evaluated during 2015 and 2016 cotton growing seasons in research farm of Punjab Agricultural University, Ludhiana, Punjab (India). A two-year field experiment was conducted and treatment included two mulch rates (0 and 6 t ha-1), three irrigation regimes (Irrigation water to cumulative pan evaporation ratio 0.2, 0.3 and 0.4) and four nitrogen rates (0, 50, 100 and 150 Kg ha-1) in factorial split plot design. Mulching has positive role in minimizing the effect of stress. Leaf water potential was higher under mulched crop over no mulched crop. Crop residue mulched canopy was 1.9-3.0, 1.7-2.3 and 1.8-3.0 °C cooler than the no mulched (stressed) canopy at I0.4, I0.3 and I0.2 irrigation regimes. There was significantly increase in SPAD value with increasing irrigation input and in order of I0.4> I0.3> I0.2 throughout the growing season. The SPAD value with mulch plot was significantly higher than the without mulch and the improvement was 2.3, 3.8, and 3.5 at 55, 82 and 110 DAS. Nitrogen rates significantly influenced the NDVI values at 55, 78 and 99 DAS. Nitrogen application also significantly increased SPAD value and with increased nitrogen rates SPAD value increased.